2023
DOI: 10.1051/0004-6361/202345980
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning algorithm for reliably predicting active galactic nucleus absorbing column densities

Abstract: We present a new method for predicting the line-of-sight column density (NH) values of active galactic nuclei (AGN) based on mid-infrared (MIR), soft X-ray, and hard X-ray data. We developed a multiple linear regression machine learning algorithm trained with WISE colors, Swift-BAT count rates, soft X-ray hardness ratios, and an MIR–soft X-ray flux ratio. Our algorithm was trained off 451 AGN from the Swift-BAT sample with known NH and has the ability to accurately predict NH values for AGN of all levels of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…NuSTAR (Harrison et al, 2013) provided the first focusing hard X-ray telescope in orbit, opening a new era into the pursuit and understanding of heavily obscured accretion onto supermassive black holes (see Section 2). To date, NuSTAR has provided the most sensitive insights into the X-ray obscuration of the brightest Compton-thick AGN known (Arévalo et al, 2014;Puccetti et al, 2014;Bauer et al, 2015;Puccetti et al, 2016), as well as the wider population identified previously with wide-field hard X-ray monitoring surveys (Annuar et al, 2015;Gandhi et al, 2017;Marchesi et al, 2017;2019b;Torres-Albà et al, 2021;Traina et al, 2021;Zhao et al, 2021;Pizzetti et al, 2022;Silver et al, 2022;Tanimoto et al, 2022). NuSTAR has also enabled unambiguous Compton-thick line-of-sight column density classifications for a bulk of the previously published candidate Compton-thick sources that had not been detected > 10 keV before (Baloković et al, 2014;Gandhi et al, 2014;Ptak et al, 2015;Boorman et al, 2016;Masini et al, 2016;Annuar et al, 2017;LaMassa et al, 2019;Kammoun et al, 2020).…”
Section: The Prevalence Of Obscured Accretion Onto Supermassive Black...mentioning
confidence: 99%
“…NuSTAR (Harrison et al, 2013) provided the first focusing hard X-ray telescope in orbit, opening a new era into the pursuit and understanding of heavily obscured accretion onto supermassive black holes (see Section 2). To date, NuSTAR has provided the most sensitive insights into the X-ray obscuration of the brightest Compton-thick AGN known (Arévalo et al, 2014;Puccetti et al, 2014;Bauer et al, 2015;Puccetti et al, 2016), as well as the wider population identified previously with wide-field hard X-ray monitoring surveys (Annuar et al, 2015;Gandhi et al, 2017;Marchesi et al, 2017;2019b;Torres-Albà et al, 2021;Traina et al, 2021;Zhao et al, 2021;Pizzetti et al, 2022;Silver et al, 2022;Tanimoto et al, 2022). NuSTAR has also enabled unambiguous Compton-thick line-of-sight column density classifications for a bulk of the previously published candidate Compton-thick sources that had not been detected > 10 keV before (Baloković et al, 2014;Gandhi et al, 2014;Ptak et al, 2015;Boorman et al, 2016;Masini et al, 2016;Annuar et al, 2017;LaMassa et al, 2019;Kammoun et al, 2020).…”
Section: The Prevalence Of Obscured Accretion Onto Supermassive Black...mentioning
confidence: 99%